Does climate change transform military medicine and defense medical support? - Yohan Robinson; Yohan Robinson; Amir Khorram-Manesh; Niclas Arvidsson; Niclas Arvidsson; Cave Sinai; Cave Sinai; Fabian Taube; Fabian Taube (Frontiers Media S.A., 2023)
BackgroundClimate change has effects on multiple aspects of human life, such as access to food and water, expansion of endemic diseases as well as an increase of natural disasters and related diseases. The objective of this review is to summarize the current knowledge on climate change effects on military occupational health, military healthcare in a deployed setting, and defense medical logistics.MethodsOnline databases and registers were searched on August 22nd, 2022 and 348 papers retrieved, published between 2000 and 2022, from which we selected 8 publications that described climate effects on military health. Papers were clustered according to a modified theoretical framework for climate change effects on health, and relevant items from each paper were summarized.ResultsDuring the last decades a growing body of climate change related publications was identified, which report that climate change has a significant impact on human physiology, mental health, water- and vector borne infectious diseases, as well as air pollution. However, regarding the specific climate effects on military health the level of evidence is low. The effects on defense medical logistics include vulnerabilities in the cold supply chain, in medical devices functioning, in need for air conditioning, and in fresh water supply.ConclusionsClimate change may transform both the theoretical framework and practical implementations in military medicine and military healthcare systems. There are significant knowledge gaps on climate change effects on the health of military personnel in operations of both combat and non-combat nature, alerting the need for prevention and mitigation of climate-related health issues. Further research within the fields of disaster and military medicine is needed to explore this novel field. As climate effects on humans and the medical supply chain may degrade military capability, significant investments in military medical research and development are needed.